The effect of diabetic foot exercise on the effectiveness of blood sugar levels in type 2 diabetes mellitus patients at The Tamalanrea Jaya Health Center Makassar City - Syaipuddin Syaipuddin; Yasir Haskas; Suhartatik; Sitti Nurbaya; Sulastri (Science Midwifery, 2023)
Diabetes mellitus (DM) which we call diabetes is a series of symptoms, both absolute and relative, caused by an increase in blood sugar (glucose) levels due to insulin deficiency. DM is a chronic degenerative disease whose number continues to increase from year to year. If this is allowed to continue without therapy can cause complications, to prevent this, one of the pillars of diabetes management is physical exercise or exercise, namely diabetic foot exercise. The purpose of the study was to determine the effect of diabetic foot exercises on the effectiveness of blood sugar levels of type 2 diabetes mellitus patients in the work area of the Tamalanrea Jaya health center, Makassar City. The research design used is pre-experimental with one group pretest post test design. The sampling technique was carried out with a total of 32 samples. The results of the study using the t-test paired samples test obtained a p value = 0.000 < α = 0.05. The conclusion of the research results shows the influence of diabetic foot exercises on the effectiveness of sugar levels in type 2 diabetes mellitus patients in the work area of the Tamalanrea Jaya health center, Makassar City. This is in accordance with research conducted by Nuraeni & Arjita in 2019, showing that diabetic foot exercises are very easy to do (can be indoors or outdoors) and do not require a long time (only about 15-30 minutes) and do not require complicated equipment (chairs and a piece of old newspaper). At least foot gymnastics movements are done 3 times a week, but it would be better if they were done every day. Doing regular foot exercises can help a diabetes mellitus patient regulate his blood glucose levels within a normal and stable range.